Effects of Resistance Exercise Using Theraband with Weighted Cuff Resistance on Fall Risk and Balance among the Geriatric Population: A Randomised Controlled Trial - Ghazala Khan; Meena Gupta; Altaf Hussain Mir (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Balance impairments and an increased fall risk are common concerns among individuals with various health conditions. Resistance exercise has shown potential in improving balance and reducing fall risk. Aim: To determine the effects of home-based Thera-Band resistance training in reducing the risk of falls among the geriatric population and to compare it with weight-cuff resistance training. Materials and Methods: A Randomised Controlled Trial (RCT) was conducted at the Amity Institute of Health and Applied Science, Noida, India, from November 2022 to April 2023. The intervention period spanned four weeks, and a total of thirtythree subjects were enrolled in the study. The participants were divided into three groups: Group A, Group B, and Group C. Group A performed resistance exercises using weight cuffs combined with standard balance training, Group B performed resistance training with Thera-Band combined with standard balance training, and Group C received standard balance exercises alone. The effects of the interventions on fall risk reduction were assessed using the Berg Balance Scale (BBS), Timed Up and Go (TUG), and Fall Efficacy Scale (FES) among the geriatric population. Paired t-tests were employed to compare pre- and post-intervention data within each group, determining significant changes within each group over the intervention period. Analysis of variance (ANOVA) was utilised to assess between-group effects of the different interventions. Results: The FES scores were assessed pre- and postintervention for each group. Group B (Thera-Band) demonstrated significantly better outcomes in fall efficacy compared to Group A (Weight-cuff) (p<0.01) and Group C (p<0.01). For balance assessment using the BBS, both Group A and Group B showed better results compared to Group C (p<0.01). In terms of mobility assessed through the TUG test, Group B exhibited substantial improvement compared to both Group A and Group C (p<0.05). Improvements in fall efficacy, balance, and mobility were seen in Group B (Thera-Band). Conclusion: Home-based resistance training using TheraBand was found to be the most effective method for reducing the risk of falls in the geriatric population, followed by weightcuff resistance training in combination with conventional balance training. Thera-Band is not only effective but also more convenient, hassle-free, and cost-effective. The geriatric population should be provided with more multi-mode exercises that are easy to perform and have been found to be effective and helpful at their advanced age.